The Impact of Physical Workload and Personal Factors on Nutritional Status Among Manufacturing Workers: A Cross-Sectional Study - Lutfiya, Indah; Ibad, Mursyidul; Rahmawati, Nur Anisah; Damayanti, Ratih; Prasetya, Tofan Agung Eka; Al Khowwas, Ibrahim (Universitas Airlangga, 2025)
Introduction: Occupational health must be considered in the workplace. Cases of overweight and obesity among workers in the manufacturing sector have increased. This study analyzes the relationship between physical workload and personal factors related to nutritional status among manufacturing workers. Methods: This study used an observational analytic study with a cross-sectional design. The variables of this study were physical workload, nutritional status, and personal factors such as gender, educational level, exercise habits, and smoking habits. The sample in this study was 239 workers in the manufacturing industry, and it was obtained using random sampling techniques. Data were analyzed using the Spearman correlation and coefficient contingency test. Result: More than half of the total cases of overweight and obesity occur in manufacturing workers who have a low physical workload. More than half of the respondents are female, do not have a high school education, and have never exercised. Most do not have a smoking habit. The results showed that physical workload (p=0.001), exercise habits (p=0.001), gender (p=0,004), and educational level (p=0.037) were related to nutritional status. In contrast, manufacturing workers' smoking habits were not associated with nutritional status (p>0.05). Conclusion: Physical workload, exercise habits, gender, and educational level have a relationship with nutritional status among workers, it is recommended that workers must increase their exercise routine such as implementing scheduled sports shifts for workers and providing sports facilities in companies so the case of being obesity can be decreased.